Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper examines the factors behind the recent surge in capital flows in Japan. The paper presents econometric evidence on the influence of these capital flows on the medium-term dynamics of the yen. It finds that in the case of the yen-dollar rate, nontrade factors affecting capital flows are likely to delay the adjustment of the yen-dollar rate to its long-term equilibrium value. The paper also draws on recent international experiences and trends to identify and review some of the key tax issues and options for meeting these challenges.